Hydroxyl-modified porous coordination polymer material, preparation method and sulfur dioxide capture application

By designing the synthetic hydroxy-modified porous coordination polymer material PCN-2OH, the problems of high energy consumption and high solid waste in the existing flue gas desulfurization technology are solved, and efficient capture of low concentration SO2 and recycling of SO2 are achieved. The potential of SO2 adsorbents.

CN119119508AActive Publication Date: 2024-12-13DEZHOU UNIV

Patent Information

Application Number
CN202411620617.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2024-12-13
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Existing flue gas desulfurization technology generates a large amount of solid waste and consumes high energy, making it difficult to effectively remove low concentrations of SO2, and the recovered SO2 has not been used to produce valuable chemicals.

Method used

Design and synthesize a hydroxyl-modified porous coordination polymer material PCN-2OH. By modifying hydroxyl energy groups on the ligand, adjusting the size of the pore window, it can effectively selectively adsorb SO2 molecules, and use single crystal X-ray diffraction and gas adsorption. The mixed gas penetration test of fixed beds characterized its structure and performance.

Benefits of technology

The efficient capture of low concentration SO2 is achieved, providing the potential of SO2 adsorbents, with the advantages of low energy consumption and reduced solid waste, and the recycled SO2 can be used to produce sulfuric acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119508A_ABST
    Figure CN119119508A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of crystal porous material preparation and adsorption separation, and relates to a hydroxyl-modified porous coordination polymer material, a preparation method and sulfur dioxide capture application. The chemical formula of the porous coordination polymer is [Ni3 (OH) (TMBTTP) (BDC-2OH) 3], and the porous coordination polymer has a cylindrical cage, a fusiform cage, permanent pore channels, appropriate pore sizes and a hydroxyl-modified pore environment, and can provide sufficient space and rich hydrogen bond binding sites for gas molecular adsorption, so that the porous coordination polymer material is suitable for adsorption separation of SO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation and adsorption separation of crystalline porous materials, and relates to a hydroxyl-modified porous coordination polymer material, a preparation method and sulfur dioxide capture application. Background Art

[0002] my country has abundant coal reserves, and coal will continue to occupy an important position in my country's energy supply now and in the future. The exhaust gas produced by coal powder combustion contains 10~12% CO2 and 500~3000 ppm SO2. Among them, SO2 is a toxic and corrosive gas that will pose a major threat to human health and the environment. Although current flue gas desulfurization technologies can remove most of the SO2 from flue gas, they produce a large amount of solid waste and require a lot of energy. Dry, regenerable adsorbents that selectively capture SO2 under ambient conditions have attracted increasing interest and are considered to be a promising strategy for eliminating low-concentration SO2. Compared with flue gas desulfurization, this method has the advantages of low energy consumption and reduced solid waste. In addition, the recovered SO2 can be used to produce valuable chemicals such as sulfuric acid.

[0003] Porous coordination polymer (PCN) materials are crystalline porous materials assembled from metal nodes and organic molecules. Due to their high porosity, structural diversity and highly customizable pore functions, they have attracted a lot of attention in gas adsorption and are considered to be solid adsorbents with great practical prospects. For PCN materials used to effectively adsorb low-concentration gases, pore size adjustment and specific functional group modification are effective design and synthesis schemes. Summary of the invention

[0004] In view of the size and chemical properties of SO2 molecules, the present invention uses a dual-ligand cage-based PCN design synthesis strategy. By modifying the hydroxyl energy group on the ligand, it not only provides adsorption functional sites in the PCN pores, but also adjusts the window size of the pores to achieve efficient and selective adsorption of SO2 molecules. The prepared material uses single crystal X-ray diffraction, gas adsorption and fixed bed mixed gas penetration tests to systematically characterize its structure, pore properties and actual SO2 capture performance, and combines theoretical calculations to analyze the adsorption mechanism. The PCN-2OH material provided by the present invention has the potential to be developed as a SO2 adsorbent.

[0005] The present invention is achieved through the following technical solutions: The first object of the present invention is to provide a hydroxyl-modified porous coordination polymer material, the chemical formula of which is [Ni3(OH)(TMBTTP)(BDC-2OH)3], wherein TMBTTP is an organic ligand 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine (CAS No.: 2027486-17-3), and H2BDC-2OH is 2,5-dihydroxyterephthalic acid (CAS No.: 610-92-4), named PCN-2OH; The porous coordination polymer material has a cage-like microporous structure modified with hydroxyl groups.

[0006] Furthermore, from the perspective of framework connection construction, the crystal structure of PCN-2OH belongs to the trigonal system, and the space group is P6 3 / mcm , the unit cell parameters are: a = 16.9485(18) Å, b =16.9485(18) Å, c=15.019(3) Å, α = β= 90 o , γ= 120 o .

[0007] Furthermore, in the porous polymer structure of PCN-2OH, the crystallographic asymmetric structural unit comprises 1 Ni(II) ion, 1 / 3 µ3-O group, 1 BDC 2− -2OH ligand and 1 / 3 TMBTTP ligand; [Ni3(OH)(TMBTTP)(BDC-2OH)3], The Ni(II) ion is coordinated with 6 atoms in an octahedral configuration, including 4 atoms from different BDCs. 2− The carboxyl O atom of the -2OH ligand, one µ3-O atom and one N atom from the TMBTTP ligand; three adjacent Ni(II) ions are bound by a µ3-O group and six different BDCs. 2− The six carboxyl groups of the -2OH ligands are bridged to form a typical trinuclear metal cluster [Ni3(μ3-O)(COO)6]; each metal cluster is connected to the BDC 2− The -2OH ligands are alternately connected to form a three-dimensional porous structure with an acs topological configuration, and the TMBTTP ligands connect the [Ni3(μ3-O)(COO)6] clusters, further dividing them into a three-dimensional framework with a pacs topological structure.

[0008] Furthermore, in the PCN-2OH structure, there are two cage structures, spindle-shaped and cylindrical. The upper and lower vertices of the spindle cage are occupied by one [Ni3(μ3-OH)(COO)6] cluster respectively, and three [Ni3(μ3-OH)(COO)6] clusters are evenly distributed in the middle part. The vertices and the middle clusters are connected by BDC. 2− -2OH ligands, the three [Ni3(μ3-O)(COO)6] clusters in the middle are connected by TMBTTP ligands, and the distance between the vertices of the spindle cage is 14.2 Å, and the distance between the middle position is about 10.4 Å; The upper and lower planes of the cylindrical cage contain three [Ni3(μ3-O)(COO)6] clusters and one TMBTTP ligand, respectively. The wall of the cylinder consists of six BDC 2− -2OH occupies the bottom of the cylindrical cage, and the distances between the upper and lower atoms are 10.4 Å and 5.8 Å, respectively. 2− The -2OH ligands and -OH groups of metal clusters are distributed in the windows and cross-section centers of the two cage structures.

[0009] The present invention also provides a method for preparing the porous coordination polymer material, comprising the following steps: Under sealed conditions, organic ligands 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine (TMBTTP), 2,5-dihydroxyterephthalic acid (H2BDC-2OH) and nickel nitrate hexahydrate (Ni(NO3)2·6H2O) were dissolved in N , N - A mixed solution of dimethylacetamide and water, and an appropriate amount of 48 wt % tetrafluoroboric acid aqueous solution was added to adjust the acidity of the solution, and the PCN-2OH metal organic framework crystal material was obtained through a solvothermal reaction.

[0010] Further, the molar ratio of the organic ligand H2BDC-2OH, TMBTTP and the metal salt is 1:(0.2-0.5):(1-3); Each 0.1 mmol of H2BDC-2OH corresponds to 1~2.5 ml of N , N -Dimethylacetamide; 0.1~0.4 ml of deionized water for every 0.1 mmol of Ni(NO3)2·6H2O; Each 1 ml of DMA corresponds to 15-35 μl of 48 wt% tetrafluoroboric acid aqueous solution. Further, the solvothermal reaction temperature is 95-120° C., and the reaction time is 12-48 hours.

[0011] Furthermore, the porous coordination polymer material is activated by the following method: first, the synthesized material is washed three times with ethanol, and the washed sample is immersed in anhydrous ethanol solution for 24 hours, during which the ethanol is continuously stirred and replaced three times. The sample is filtered to obtain a sample, and then dried in a vacuum oven at 100°C for 4 hours to obtain an activated sample.

[0012] The present invention also provides application of the porous coordination polymer material in SO2 capture.

[0013] Beneficial technical effects of the present invention: The double-fused ring ligand metal organic framework crystal material of the present invention has a novel structure and a stable framework, and there are two types of cages: cylindrical and spindle-shaped. At 77 K, the nitrogen isotherm adsorption curve of PCN-2OH is type I, and the maximum nitrogen adsorption at pressure P / P0 = 1 is 253.5 cm 3 / g, the specific surface area calculated from the adsorption data is 966 m 2 / g, and the pore size distribution obtained from the adsorption data analysis is 4.7-12.5 Å. This permanent pore channel, suitable pore size, and hydroxyl-modified pore environment can provide sufficient space and abundant hydrogen bonding sites for the adsorption of gas molecules, making the metal-organic framework suitable for the adsorption and separation of SO2. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a photo of PCN-2OH crystals under a microscope.

[0015] Figure 2 This is a photo of PCN-2OH in powder state.

[0016] Figure 3 Figure 2 shows the coordination environment and coordination mode of the Ni metal center in PCN-2OH.

[0017] Figure 4 This is the three-dimensional framework structure diagram of PCN-2OH.

[0018] Figure 5 Figure 2 is the structural diagram of the spindle-shaped cage in PCN-2OH.

[0019] Figure 6 Figure 2 shows the structure of the cylindrical cage in PCN-2OH.

[0020] Figure 7 The powder X-ray diffraction spectra of synthesized PCN-2OH and its treatment under different conditions.

[0021] Figure 8 This is the thermal gravimetric curve of PCN-2OH.

[0022] Fig. 9This is the nitrogen adsorption-desorption isotherm of PCN-2OH at 77 K.

[0023] Fig.10 This is a comparison of the adsorption isotherms of SO2 / CO2 / N2 for PCN-2OH at 298 K.

[0024] Fig.11 This is a comparison of the adsorption isotherms of SO2 / CO2 / N2 for PCN-2OH at 308 K.

[0025] Fig.12 This is the IAST selectivity curve of PCN-2OH at 298 K.

[0026] Fig.13 Schematic diagram of the dynamic breakthrough curve of PCN-2OH to SO2 and CO2 at 25 ℃.

[0027] Fig.14 This is the adsorption heat curve of PCN-2OH for SO2 and CO2. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0029] Example 1 The organic ligand H2BDC-2OH (0.01 mmol) and TMBTTP (0.002 mmol) were weighed and ultrasonically dissolved in 0.1 ml DMA, and the metal salt Ni(NO3)2·6H2O (0.01 mmol) was dissolved in 0.02 ml deionized water. Then 1.5 μL of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure container. The metal-organic framework crystals were obtained by thermal reaction at 85 °C for 48 hours.

[0030] Example 2 The organic ligand H2BDC-2OH (0.02 mmol) and TMBTTP (0.005 mmol) were weighed and ultrasonically dissolved in 0.5 ml of DMA, and the metal salt Ni(NO3)2·6H2O (0.04 mmol) was dissolved in 0.1 ml of deionized water. Then 7.5 μL of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure container bottle. The metal-organic framework crystals were obtained by thermal reaction at 120 °C for 12 hours.

[0031] Example 3 The organic ligand H2BDC-2OH (0.05 mmol) and TMBTTP (0.02 mmol) were weighed and ultrasonically dissolved in 0.8 ml of DMA, and the metal salt Ni(NO3)2·6H2O (0.15 mmol) was dissolved in 0.6 ml of deionized water. Then 20 μL of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure container bottle. The crystals of the metal-organic framework were obtained by thermal reaction at 100 °C for 36 hours.

[0032] Example 4 The organic ligands H2BDC-2OH (0.1 mmol) and TMBTTP (0.02 mmol) were weighed and ultrasonically dissolved in 2.0 ml of DMA, and the metal salt Ni(NO3)2·6H2O (0.3 mmol) was dissolved in 1 ml of deionized water. Then 70 μL of tetrafluoroboric acid aqueous solution (52 wt%) was added and sealed in a pressure container bottle. The metal-organic framework crystals were obtained by thermal reaction at 110 °C for 32 hours.

[0033] The test results of the products obtained in the above embodiments are the same, as shown below: (1) Crystal structure determination: Single crystals of appropriate size were selected under a microscope, and data were collected on a Bruker SMART APEXII CCD diffractometer. Absorption correction was performed using the SADABS program. SHELXL-2014 was used to solve and refine the structural data for F2 using the direct method and full-matrix least squares method. The crystallographic program used the single-suite Olex2 integrated system. All non-hydrogen atoms were anisotropically refined. The positions and thermal parameters of hydrogen atoms were determined, and the structure was refined by geometric calculations. The contribution of disordered solvent molecules was processed using the SQUEEZE program implemented in PLATON. See the structure diagram. Figure 1-4 The crystallographic data are shown in Table 1.

[0034] Table 1 Crystallographic data of metal organic framework materials

[0035] Figure 1 The crystal morphology of PCN-2OH obtained in Example 1-4 under a microscope. Figure 2 The PCN-2OH material obtained in Examples 1-4 is in the form of brown powder. Figure 3 Figure 2 shows the coordination environment and coordination mode of the Ni metal center in PCN-2OH. It can be seen that the Ni(II) ion of PCN-2OH is coordinated with 6 atoms in an octahedral configuration, including 4 atoms from different BDCs. 2−The four carboxyl O atoms of each dicarboxylic acid are connected to four Ni atoms, all of which are μ2-η 1 :η 1 coordination mode.

[0036] Figure 4 The three-dimensional framework structure of PCN-2OH shows that in PCN-2OH, three adjacent Ni(II) ions are bound by one μ3-O group and six different BDCs. 2− The six carboxyl groups of the -2OH ligands bridge to form typical trinuclear metal clusters [Ni3(μ3-O)(COO)6]. These trinuclear metal clusters are alternately connected with TMBTTP ligands to form a three-dimensional framework. Figure 5 and Figure 6 The spindle cage and cylindrical cage structures in PCN-2OH are shown in Figure 1, which show that there are two cage structures in the PCN-2OH structure: spindle cage and cylindrical cage. The upper and lower vertices of the spindle cage are occupied by one [Ni3(μ3-O)(COO)6] cluster respectively, and three [Ni3(μ3-O)(COO)6] clusters are evenly distributed in the middle part. The vertices and the middle clusters are connected by BDC. 2− The three [Ni3(μ3-O)(COO)6] clusters in the middle are connected by TMBTTP ligands. The distance between the vertices of the spindle cage is about 14.2 Å, and the diameter in the middle is about 10.4 Å. The upper and lower planes of the cylindrical cage contain three [Ni3(μ3-O)(COO)6] clusters and one TMBTTP ligand, respectively. The wall of the cylindrical hole is composed of six BDCs. 2− -2OH occupies the cylindrical cage, with a base diameter and height of 10.4 and 5.8 Å, respectively.

[0037] Figure 7 The X-ray powder diffraction spectrum shows that the prepared PCN-2OH is a pure phase, and its crystal skeleton structure remains unchanged after the sample is activated by ethanol and cycled.

[0038] Figure 8 The thermogravimetric curves show that the thermal stability of the PCN-2OH framework reaches 400 ℃.

[0039] (2) Specific surface area characterization Fig. 9 The PCN-2OH framework material of the present invention is P / P N2 adsorption-desorption isotherms under the conditions of 0 = 1 and 77 K. It can be seen from the figure that the saturated N2 absorption of PCN-2OH reaches 253.5 cm 3 / g (STP). By fitting and analyzing the adsorption data, the specific surface area of ​​PCN-2OH was found to be 966 m 2 / g, and the pore size distribution is between 4.7 and 12.5 Å.

[0040] (3) Characterization of adsorption and separation performance: Fig.10 and Fig.11 The PCN-2OH framework material is at 298 K and 308 K respectively. P / P 0 is 1.0. Take 200 mg of the activated adsorbent sample and place it in a vacuum treatment at 120 °C for 3 h. After degassing, the gas adsorption isotherm test was carried out at 298 K and 308 K respectively. The steam is generated by a high-purity solvent. It can be seen from the figure that under the conditions of 298K and 1 bar, the maximum adsorption capacity of PCN-2OH material for SO2 and CO2 is 232.1cm 3 / g, 63.2 cm 3 / g. At 308K, the maximum adsorption capacity of PCN-2OH crystal material for SO2 and CO2 is 189.6 cm 3 / g,50.8cm 3 / g. At 298K and 1 bar, the maximum adsorption difference is 168.9 cm 3 / g, the adsorption difference at P = 0.1 bar reached 48.0 cm 3 These results show that PCN-2OH has significant differences in the adsorption capacity of SO2 and CO2, and has the potential for selective and preferential adsorption of SO2.

[0041] Fig.12 This is the IAST selectivity curve of the PCN-2OH framework material of the present invention for a SO2 / CO2 mixed gas at 298 K. The figure shows that under the condition of 298 K, the IAST selectivity value of PCN-2OH for SO2 / CO2 is between 6.03 and 59.66.

[0042] Fig.13The penetration curve of the PCN-2OH framework material of the present invention for separating a SO2 / CO2 mixed gas. At 298 K and a pressure of 1 bar, a SO2 / CO2 mixed gas (SO2 / CO2 / N2, v:v:v=0.2 / 50 / 49.8, SO2: 2000 ppm) passed through a quartz tube containing 0.5 g of PCN-2OH at a flow rate of 100 mL / min. From the penetration curve, it can be seen that CO2 first passed through the MOF material, and SO2 gas molecules were detected after a certain interval. This further reflects the good SO2 separation ability of the material. The penetration time difference of the mixed gas in PCN-2OH is 35.44 min. The results show that the porous coordination polymer crystal material has application potential for separating SO2 / CO2 mixed gases.

[0043] Fig.14 The adsorption heat curves of PCN-2OH framework material for SO2 and CO2 are shown in Figure 2. In the porous coordination polymer crystal material, the Q of SO2 st The value is 59.32 kJ / mol, which is higher than the corresponding value for CO2, which means that the material has a stronger affinity for SO2 than CO2.

Claims

1. A hydroxyl-modified porous coordination polymer material, characterized in that: The chemical formula is [Ni3(OH)(TMBTTP)(BDC-2OH)3], where TMBTTP is the organic ligand 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine, and H2BDC-2OH is 2,5-dihydroxyterephthalic acid, named PCN-2OH; The porous coordination polymer material has a cage-like microporous structure modified with hydroxyl groups.

2. The hydroxyl-modified porous coordination polymer material according to claim 1, characterized in that: From the perspective of framework connection construction, the crystal structure of PCN-2OH belongs to the trigonal system, and the space group is P6 3 / mcm , the unit cell parameters are: a =16.9485(18) Å, b =16.9485(18) Å, c=15.019(3) Å, α = β = 90 o , γ = 120 o .

3. The hydroxyl-modified porous coordination polymer material according to claim 1, characterized in that: In the porous polymer structure of PCN-2OH, its crystallographic asymmetric structural unit includes 1 Ni(II) ion, 1 / 3 µ3-O group, 1 BDC 2− -2OH ligand and 1 / 3 TMBTTP ligand; [Ni3(OH)(TMBTTP)(BDC-2OH)3], The Ni(II) ion is coordinated with 6 atoms in an octahedral configuration, including 4 atoms from different BDCs. 2− The carboxyl O atom of the -2OH ligand, one µ3-O atom and one N atom from the TMBTTP ligand; three adjacent Ni(II) ions are bound by a µ3-O group and six different BDCs. 2− The six carboxyl groups of the -2OH ligands are bridged to form a typical trinuclear metal cluster [Ni3(μ3-O)(COO)6]; each metal cluster is connected to the BDC 2− The -2OH ligands are alternately connected to form a three-dimensional porous structure with an acs topological configuration, and the TMBTTP ligands connect the [Ni3(μ3-O)(COO)6] clusters, further dividing them into a three-dimensional framework with a pacs topological structure.

4. The hydroxyl-modified porous coordination polymer material according to claim 1, characterized in that: In the PCN-2OH structure, there are two cage structures, spindle-shaped and cylindrical. The upper and lower vertices of the spindle cage are occupied by one [Ni3(μ3-OH)(COO)6] cluster respectively, and three [Ni3(μ3-OH)(COO)6] clusters are evenly distributed in the middle. The vertices and the middle clusters are connected by BDC. 2− -2OH ligands, the three [Ni3(μ3-O)(COO)6] clusters in the middle are connected by TMBTTP ligands, and the distance between the vertices of the spindle cage is 14.2 Å, and the distance between the middle position is about 10.4 Å; The upper and lower planes of the cylindrical cage contain three [Ni3(μ3-O)(COO)6] clusters and one TMBTTP ligand, respectively. The wall of the cylinder consists of six BDC 2− -2OH occupies the bottom of the cylindrical cage, and the distances between the upper and lower atoms are 10.4 Å and 5.8 Å, respectively. 2− The -2OH ligands and -OH groups of metal clusters are distributed in the windows and cross-section centers of the two cage structures.

5. A method for preparing a hydroxyl-modified porous coordination polymer material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Under sealed conditions, organic ligands 4,4',4'-(2,4,6-trimethylbenzene-1,3,5-triphenyl)tripyridine (TMBTTP), 2,5-dihydroxyterephthalic acid (H2BDC-2OH) and nickel nitrate hexahydrate (Ni(NO3)2·6H2O) were dissolved in N , N - A mixed solution of dimethylacetamide and water, and 48 wt % tetrafluoroboric acid aqueous solution was added to adjust the acidity of the solution, and the PCN-2OH metal organic framework crystal material was obtained through a solvothermal reaction.

6. The method for preparing a hydroxyl-modified porous coordination polymer material according to claim 5, characterized in that: The molar ratio of the organic ligand H2BDC-2OH, TMBTTP and the metal salt is 1:(0.2-0.5):(1-3).

7. The method for preparing a hydroxyl-modified porous coordination polymer material according to claim 5, characterized in that: Each 0.1 mmol of H2BDC-2OH corresponds to 1~2.5 ml of N , N -dimethylacetamide; 0.1~0.4 ml of deionized water for every 0.1 mmol of Ni(NO3)2·6H2O; 15~35 μl of 48 wt% tetrafluoroboric acid aqueous solution for every 1 ml of DMA.

8. The method for preparing a hydroxyl-modified porous coordination polymer material according to claim 5, characterized in that: The temperature of the solvent thermal reaction is 95-120° C., and the reaction time is 12-48 hours.

9. Use of the hydroxyl-modified porous coordination polymer material according to any one of claims 1 to 4 in SO2 capture.

Citation Information

Patent Citations

  • Double-fused-ring ligand MOF crystal material, preparation method thereof and application of double-fused-ring ligand MOF crystal material in separation of benzene / cyclohexane

    CN118005947A

  • Porous double-fused-ring ligand coordination polymer material, preparation method thereof and application of porous double-fused-ring ligand coordination polymer material in separation of toluene / methylcyclohexane

    CN118063789A

  • Porous coordination polymer crystal material, preparation method thereof and application of porous coordination polymer crystal material in adsorption removal of SO2

    CN118085321A

  • Novel metal-organic framework having porous structure formed from zirconium cluster secondary building unit and multi-binding linker

    WO2019231297A1

Cited By

  • Fluorine-modified porous framework crystal material, preparation method thereof and application of fluorine-modified porous framework crystal material in acetylene / carbon dioxide separation

    CN119608128A

  • A fluorine-modified porous framework crystal material, a preparation method thereof, and acetylene / carbon dioxide separation application

    CN119608128B

  • Cationic indium-based metal organic framework material, preparation method and sulfur dioxide trapping and storage application

    CN122325780A